INPATIENT VS OUTPATIENTS LABOR INDUCTION : A COMPREHENSIVE SYSTEMATIC REVIEW - Ramadhan, Mu’arif; Putu Arianta, Yohanes (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Labor induction can take a long period, anywhere from a few hours to several days, especially in nulliparous women. Worldwide, the use of mechanical or pharmaceutical treatments for outpatient cervical ripening is becoming more and more common. Aims : This systematic review is to review the comparison of outpatient with inpatient labor induction. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed and SAGEPUB, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMded database, the results of our search brought up 83 articles, whereas the results of our search on SAGEPUB brought up 605 articles, our search on SCIENCE DIRECT brought up 470 articles. The results of the search conducted for the last year of 2014 yielded a total 17 articles for PubMed, 155 articles for SAGEPUB and 122 articles for SCIENCE DIRECT. In the end, we compiled a total of 8 papers, 4 of which came from PubMed, 2 of which came from SAGEPUB and 2 of which came from SCIENCE DIRECT. We included eight research that met the criteria. Conclusion: In summary, in modern obstetrics, when labor is being induced in an increasing percentage of pregnancies, outpatient induction for low-risk women offers a safe, practical, and successful alternative to hospital induction. This is especially true in places with abundant resources. It should be given more widespread consideration.